The validity and utility of violence risk assessment tools to predict patient violence in acute care settings: An integrative literature review - De Jong, Gideon (2019)
To examine risk assessment tools to predict patient violence in acute care settings. An integrative review of the literature. Five electronic databases – CINAHL Plus, MEDLINE, OVID, PsycINFO, and Web of Science were searched between 2000 and 2018. The reference list of articles was also inspected manually. The PICOS framework was used to refine the inclusion and exclusion of the literature, and the PRISMA statement guided the search strategy to systematically present findings. Forty-one studies were retained for review. Three studies developed or tested tools to measure patient violence in general acute care settings, and two described the primary and secondary development of tools in emergency departments. The remaining studies reported on risk assessment tools that were developed or tested in psychiatric inpatient settings. In total, 16 violence risk assessment tools were identified. Thirteen of them were developed to assess the risk of violence in psychiatric patients. Two of them were found to be accurate and reliable to predict violence in acute psychiatric facilities and have practical utility for general acute care settings. Two assessment tools were developed and administered in general acute care, and one was developed to predict patient violence in emergency departments. There is no single, user-friendly, standardized evidence-based tool available for predicting violence in general acute care hospitals. Some were found to be accurate in assessing violence in psychiatric inpatients and have potential for use in general acute care, require further testing to assess their validity and reliability